2016
DOI: 10.17126/joralres.2016.057
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation and detection methods of EGFR in oral cancer. A narrative review.

Abstract: Epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein, with an intracellular domain and tyrosine kinase function (TK) involved in cell proliferation. Dysfunctions in EGFR signaling pathways have been associated with oral malignant tumors such as oral squamous cell carcinoma (OSCC). Dysfunctions of EGFR may result from: increased EGF ligand; EGFR overexpression and copy number gain of the EGFR gene (EGFR CNG); EGFR mutations; failure in the downregulation of EGFR; and EGFR crosstalk. Of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Over the years, numerous techniques, such as IHC, fluorescence in situ hybridization (FISH), and PCR, have been used to identify the overexpression of EGFR, EGFR copy number gains (CNG), and EGFR mutations. However, numerous studies have employed IHC because of its ease and simplicity [ 32 ]. Studies evaluating the expression of EGFR in OSCC and leukoplakia have shown a significant correlation in OSCC, when compared to leukoplakia [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, numerous techniques, such as IHC, fluorescence in situ hybridization (FISH), and PCR, have been used to identify the overexpression of EGFR, EGFR copy number gains (CNG), and EGFR mutations. However, numerous studies have employed IHC because of its ease and simplicity [ 32 ]. Studies evaluating the expression of EGFR in OSCC and leukoplakia have shown a significant correlation in OSCC, when compared to leukoplakia [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scientific research on the anticancer properties of certain plants highlights their major phytochemical compounds and mechanisms of action against oral cancer. Notably, curcumin, an active constituent of turmeric, has been shown to effectively impede cancer proliferation and metastasis by disrupting EGFR signaling pathways, particularly by blocking EGFR phosphorylation (Somarriva et al, 2016).…”
Section: Gene Targets Of Plant Bioactives Against Oral Cancermentioning
confidence: 99%